The Impact of Organizational Commitment on Human Resource Satisfaction in Iraqi Tourism Education Institutions (The Peerian Journal, 2026)
This study aims to explore the impact of organizational commitment on human resource satisfaction in understanding the nature of this relationship. It poses a central problem concerning how to utilize organizational commitment as a strategic approach to raising human resource satisfaction levels. This is achieved through an analysis of the behaviors of teaching staff in Iraqi tourism education institutions, using (130) questionnaires. The study included the independent variable, represented by (organizational commitment) with its dimensions (affective commitment, normative commitment, and continuity commitment), which reflect the level of human resource connection to the educational institution from a psychological and behavioral perspective. The dependent variable was (human resource satisfaction), which includes its dimensions (job satisfaction, satisfaction with managers, satisfaction with colleagues, satisfaction with wages and salaries, and satisfaction with promotions). The study adopted the descriptive-analytical approach as the most suitable methodological framework for achieving the study's objectives. The hypotheses were tested using the SPSS and AMOS statistical programs to verify the existence of a direct effect of organizational commitment on human resource satisfaction. One of the most important findings of the study is that there is a significant effect of organizational commitment on human resource satisfaction